Analisis Faktor - Faktor Yang Mempengaruhi LoyalitasPelanggan Ahass Cahaya Sakti MotorDi Karangpandan - Andira, Andesva Farah; , Drs. M. Nasir, MM (2017)
This research aim to test influence of factor of service quality, consumer attitude, and location to having an effect on to customer loyality use service of AHASS Cahaya Sakti Motorof Karangpandan. Population and sample which are used in this research oneof who come using service of AHASS CahayaSakti Motorin Karangpandan counted 40 respondent. The hypothesis tested in this research use analyzer test of validity, reliabilities test, the classical assumption test, analysis of doubled linear regression, t test, F test, and coefficient of determines (R2). Result of research indicate that the service qualityhave an effect on positive and significant to customer loyality, consumer attitude have an effect on positive and significant to customer loyality, and location have an effect on positive and significant to customer loyality. The third of examination of the hypothesis can be proved with test t. Service quality, consumer attitude, and location by together have an effect on positive influence and significant to customer loyality, this matter can be proved with test F. Result of examination of coefficient of determines (R2) indicate that the quality of service, consumer attitude, and location can explain customer loyality variability equal to 54,1%.